2007
DOI: 10.1158/0008-5472.can-06-2969
|View full text |Cite
|
Sign up to set email alerts
|

Serine-Arginine Protein Kinase 1 Overexpression Is Associated with Tumorigenic Imbalance in Mitogen-Activated Protein Kinase Pathways in Breast, Colonic, and Pancreatic Carcinomas

Abstract: Aberrant patterns of pre-mRNA processing are typical of human malignancies, yet the mechanisms responsible for these changes remain undefined. We have recently shown overexpression of a core splice regulatory protein, serinearginine protein kinase 1 (SRPK1), in dysplastic and neoplastic pancreatic ductular cells. In the present study, we have established that SRPK1 levels are similarly up-regulated in breast and colonic tumors where its expression increases coordinately with tumor grade. Targeting SRPK1 for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
154
2
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(191 citation statements)
references
References 41 publications
15
154
2
20
Order By: Relevance
“…Silencing of LARP1 increased apoptosis in HeLa cells (43). SRPK1 (SRSF protein kinase 1) functions in alternative splicing and has been implicated in many cancer types (44,(65)(66)(67)(68). Silencing of SRPK1 increased apoptotic potential in breast and colonic tumor cell lines (44) and decreased proliferative capacity in leukemic cells (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing of LARP1 increased apoptosis in HeLa cells (43). SRPK1 (SRSF protein kinase 1) functions in alternative splicing and has been implicated in many cancer types (44,(65)(66)(67)(68). Silencing of SRPK1 increased apoptotic potential in breast and colonic tumor cell lines (44) and decreased proliferative capacity in leukemic cells (69).…”
Section: Discussionmentioning
confidence: 99%
“…3A). CCNG1, MTHFD2, LARP1, and SRPK1 were selected on the basis of their previous implications in breast cancer (41)(42)(43)(44), whereas AP3B1 and MTHFD1L were selected as potential biomarkers. All of these genes were predicted to have one miR-9 binding site, except MTHFD2, which has two predicted miR-9 binding sites (Fig.…”
Section: Down-regulated Genes Responsive To Mir-9 Overexpression Are mentioning
confidence: 99%
“…SRPK1 is known to activate SR proteins by phosphorylation enabling them to migrate to the nucleus and participate in the splicing process (14). SRPK1 has been reported to be up-regulated in several human cancers including colon and breast where a knockdown of SRPK1 was shown to increase the number of cells undergoing apoptosis (13). Splicing factor binding prediction analysis showed that SRSF1 binding motifs were found primarily in exon 4B of SLC39A14, which could explain the increased presence of 4B when either SRPK1 or SRSF1 is up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…AS plays a critical role during development, and defects in AS have been implicated in numerous human diseases, including cancer (10 -12). Several SR proteins are activated by phosphorylation of their serines by SRSF protein kinase 1 (SRPK1), which is up-regulated in colon, breast, and pancreatic cancer (13). The best described SRPK1 target is serine/arginine-rich splicing factor 1 (SRSF1, formerly known as SF2/ASF) (14,15), an essential splicing factor that participates in both constitutive and AS, and which was recently shown to be a proto-oncogene (12) supporting the involvement of AS in cancer development.…”
Section: Most Colorectal Cancers (Crc)mentioning
confidence: 99%
“…The over-expression in old HHR of the guanine nucleotide binding protein gene (Gng5), Rab12 (a member of the Ras oncogene family) and mitogen activated protein kinase 1 (Mapk1) further suggests a role for the Ras/ MAPK signaling pathway in the etiology of cardiac enlargement in the HHR. Evidence that MAPK1 (27)(28)(29), MAPK14 (30,31) and MAP2K4 (32) are involved in normal and abnormal tissue growth further strengthens the possibility that these are key enzymes in the cardiotrophic process in the HHR. However, the cause and effect relationship between the activity of these enzymes and the elevated cardiac size of the HHR remains to be determined.…”
Section: Discussionmentioning
confidence: 80%